EFECTIVENESS OF GREEN BETEL LEAF EXTRACT (Piper betle L.) AND LIQUID SMOKE AGAINST Plutella xylostella IN CHICORY PLANTS - Mahmuda, Jevina Dewi; Haryadi, Nanang Tri (Universitas Trilogi, 2023)
Chicory is one of the horticultural crops that is widely cultivated in Indonesia. Plutella xylostella are the main pests of the chicory plant. The attack damaged P. xylostella by 58-100%. The intensive use of chemical pesticides in pest control can use damage the environment and humans. Utilization of green betel leaves extract and liquid smoke in an alternative control of P.xylostella. This study aims to determine the ability of green betel leaf extract and liquid smoke to P. xylostella on the laboratory scale. The study was conducted with 7 treatments, namely, control = 0%, green betel leaf concentrations of J1 = 10%, J2 = 15%, J3 = 15%, and liquid smoke concentrations of J4 = 10%, J5 = 15%, and J6 = 20%, and repeated 4 times. The results showed that the application of green betel leaf extract and liquid smoke at a concentration of 20% caused mortality of P. xylostella of 87.5% and 100%. This is because green betel leaves contain tannins and alkaloid compounds that inhibit cell and nerve metabolism in the larvae P. xylostella which occurs continuously and causes death. Liquid smoke contains phenolic compounds that cause respiratory problems in the larvae of P. xylostella and if swallowed can cause systemic poisoning. Green leaf extract with a concentration of 3.26% and liquid smoke with a concentration of 0.34% effectively killed 50% of the larvae P. xylostella.